2011
DOI: 10.1021/jp201411y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aligned Polyaniline Belts by Interfacial Control Approach

Abstract: Aligned polyaniline (PANI) belts doped with dodecatungstosilic acid (H4SiW12O40, abbreviated as SiW12) are synthesized by interfacial control method without surfactants or templates. The structure and morphology of the PANI are characterized by Fourier transform infrared (FT-IR) spectra, X-ray diffraction (XRD) patterns, and scanning electron microscope images (SEM). SiW12, as a doping-acid replacing HCl and offering a strong adhesive action between itself and water molecules, plays an important role in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 86 publications
2
18
0
Order By: Relevance
“…Amongst many routes, polymerization of aniline through interfacial polymerization has been reported to be a good choice to obtain PANI with controlled properties, and without the need of any post treatment [18]. The method is considered to provide an ideal confined environment for the growth of polymer exhibiting different morphological features, and has been successfully employed by different groups to obtain polymeric materials in the form of nanoneedles, nanofibers, or nanorods, which have successfully been utilized for their supercapacitive properties [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst many routes, polymerization of aniline through interfacial polymerization has been reported to be a good choice to obtain PANI with controlled properties, and without the need of any post treatment [18]. The method is considered to provide an ideal confined environment for the growth of polymer exhibiting different morphological features, and has been successfully employed by different groups to obtain polymeric materials in the form of nanoneedles, nanofibers, or nanorods, which have successfully been utilized for their supercapacitive properties [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Since it shows potential dependent variable oxidation states, interconversion of these leads to a very high theoretical capacitance value. Literature shows that ample amount of research has been performed using PANI in the supercapacitor application 39 which depends on morphology 40 41 . Its morphology as well as the electrical and physical properties depend on synthesis conditions 42 43 44 especially on the type of acid dopant used.…”
mentioning
confidence: 99%
“…12,13 PANI has been extensively studied due to its interesting electrochemical property, 14 simple preparation and low cost. 15 Recently, many attempts have been made on the preparation of nanostructured PANI [16][17][18] and the exploration of their sensing application. [19][20][21][22] From the evaluation of sensing performance achieved by different nanostructures, it is indicated that the surface/volume ratio of nanomaterials plays a key role in achieving better performance.…”
Section: Introductionmentioning
confidence: 99%